2019
DOI: 10.3389/fbioe.2019.00081
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic System for Studying the Effects of Disturbed Flow on Endothelial Cells

Abstract: Arterial endothelium experience physical stress associated with blood flow and play a central role in maintaining vascular integrity and homeostasis in response to hemodynamic forces. Blood flow within vessels is generally laminar and streamlined. However, abrupt changes in the vessel geometry due to branching, sharp turns or stenosis can disturb the laminar blood flow, causing secondary flows in the form of vortices. Such disturbed flow patterns activate pro-inflammatory phenotypes in endothelial cells, damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 44 publications
5
51
0
Order By: Relevance
“…The main obstacle in trying to answer these questions from the available literature, is that up to this point, turbulent flow (referred to in most of the literature as disturbed flow) is considered to be pathologic as opposed to laminar flow 84,85 . Moreover, on most studies that discussed the differences between laminar and turbulent flow regimes on endothelial mechanobiology, both laminar and turbulent flows were at different WSS values 8,86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…The main obstacle in trying to answer these questions from the available literature, is that up to this point, turbulent flow (referred to in most of the literature as disturbed flow) is considered to be pathologic as opposed to laminar flow 84,85 . Moreover, on most studies that discussed the differences between laminar and turbulent flow regimes on endothelial mechanobiology, both laminar and turbulent flows were at different WSS values 8,86,87 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the protective effects of GPR81 against oxidative stress, inflammation, and attachment of monocytes to endothelial cells are likely to be robustly suppressed in atherosclerosis‐prone sites, such as bifurcations and other areas of the vasculature exposed to OSS patterns. Recent research has demonstrated the important role of the activation of such mechanotransduction pathways in endothelial cells . The cessation of blood flow, aberrant flow patterns, shear stress, and OSS were shown to induce redox signaling, inflammatory response, and a shift in endothelial cells toward a pathological phenotype, thereby promoting endothelial dysfunction .…”
Section: Discussionmentioning
confidence: 99%
“…PDMS-hydrogel hybrid devices can incorporate branching and bifurcating regions of special interest for capillary splitting and other remodeling events due to the different flow patterns occurring at these sites. This type of devices have recently been used to produce impinging bifurcating fluid flow, laminar shear stress and transvascular fluid flow (Akbari et al, 2018) and also controllable disturbed flow patterns for the study of its effects on actin stress fiber and endothelial cell orientation (Tovar-Lopez et al, 2019). But how exactly does the direction, slope and average magnitude of shear stress gradients affect endothelial cell biological and molecular responses needs still to be understood.…”
Section: In Vitro Systems For Analysis Of Microvascular Remodeling Unmentioning
confidence: 99%